Aphasic variant of Alzheimer disease: Clinical, anatomic, and genetic features. (27th September 2016) - Rogalski, Emily; Sridhar, Jaiashre; Rader, Benjamin; Martersteck, Adam; Chen, Kewei; Cobia, Derin; Thompson, Cynthia K.; Weintraub, Sandra; Bigio, Eileen H.; Mesulam, M.-Marsel
Abstract : Objective: To identify features of primary progressive aphasia (PPA) associated with Alzheimer disease (AD) neuropathology. A related objective was to determine whether logopenic PPA is a clinical marker for AD. Methods: A total of 139 prospectively enrolled participants with a root diagnosis of PPA constituted the reference set. Those with autopsy or biomarker evidence of AD, and who had been evaluated at mild disease stages (Aphasia Quotient ≥85), were included (n = 19). All had quantitative language testing and APOE genotyping. Fifteen had MRI morphometry. Results: Impaired word-finding was the universal presenting complaint in the aphasic AD group. PPA clinical subtype was logopenic (n = 13) and agrammatic (n = 6). Fluency, repetition, naming, and grammaticality ranged from preserved to severely impaired. All had relative preservation of word comprehension. Eight of the 15 aphasic participants with AD showed no appreciable cortical atrophy at the individual level on MRI. As a group, atrophy was asymmetrically concentrated in the left perisylvian cortex. APOE ε4 frequency was not elevated. Conclusions: There is a close, but not obligatory, association between logopenic PPA and AD. No language measure, with the possible exception of word comprehension, can confirm or exclude AD in PPA. Biomarkers are therefore essential for diagnosis. Asymmetry of cortical atrophy and normal APOE ε4 prevalence constitute deviations from typical AD. These and additional neuropathologic features suggest that AD has biological subtypes, one of which causes PPA. Better appreciation of this fact should promote the inclusion of individuals with PPA and positive AD biomarkers into relevant clinical trials.